Comparison of Closed Versus Open Interlocking Nail Femur: A Retrospective Cohort Study in a Tertiary Care Hospital (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To compare the results of closed interlocking nail shaft of femur versus open interlocking nail in terms of union, non-union and infection rate.Methods: We conducted this retrospective Cohort study in Department of Orthopedics Jinnah Medical College Hospital Karachi and Dow University Hospital- Ojha Campus Karachi. The medical record of all patients meeting the inclusion criteria and operated for interlocking nails(closed/open) shaft of femur in the time period extending from 23rd February 2018 to 3rd March 2019 were included in our study. The demographic details, radiographs, operative notes and follow up records of both groups were noted. The post-operative results of union, non-union and infection at final evaluation at one year were compared in both groups. Chi square test was applied and P value calculated. P value < 0.05 was considered significant.Results: The medical record of 116 patients with mean age 31.1±8 were examined. Closed interlocking nail (group A) was done in 62 patients with mean age 31.1±7.9 years(range 20 to 55 years) while fracture site was opened(group B) in 54 patients with mean age 31.2±8.2years(range 19 to 57 years. The average time of radiological union was 20.5 ±3 weeks in closed versus  26.3±6 weeks in open nailing(  P value